“Actividad biológica de las lectinas obtenidas de semillas del achotillo (Nephelium lappaceum) y uvilla (Physalis peruviana), Riobamba, 2019 - 2020” - Castro Cabrera, Jocelyne Ángela (2020)
The main objective of this research project was to determine the biological activity of the phytoagglutinins (lectins) obtained from the seeds of achotillo (Nephelium lappaceum) and uvilla (Physalis peruviana) in Riobamba, the extract of each fruit was obtained by means of mechanical disruption adding 15 mL of Physiological Saline Solution, it was incubated, subsequently filtered through a fine nylon fabric and finally centrifuged using a conventional centrifuge to obtain a clear supernatant. The biological activity of the phytoagglutinins was determined evaluating in the aqueous extract of the fruits, the haemagglutinating activity with 0.1 ml of suspension of erythrocytes of blood groups A, B and O, anticoagulant activity on platelet poor plasma with the measurement of TP and aPTT and finally antimicrobial activity with the agar diffusion method using the Kirby Bauer technique on the bacterial strains Escherichia coli, Staphylococcus aureus and Enterococcus faecalis. The results obtained from haemagglutination demonstrated a high ability of lectins to bind red blood cells from blood groups A, B and O, on the other hand, no effect on the coagulation proteins of the extrinsic pathway measured through Prothrombin Time (TP) was established, however, the anticoagulant action on the coagulation proteins of the intrinsic pathway measured through the activated Thromboplastin Partial Time (aPTT) revealed a highly significant prolongation with the achotillo extract, finally the absence of antimicrobial activity by both extracts on the bacterial strains evaluated in this study. Keywords: